Bader charge distribution of the 1T-MnO2 monolayer, where Q is the charge of the free atom, Q* is the charge of the bonded atom, ∆Q the charge variation, and n the atomic charge density. - Julieth V. Dita-Casiano (22622758) (2025)
Bader charge distribution of the 1T-MnO2 monolayer, where Q is the charge of the free atom, Q* is the charge of the bonded atom, ∆Q the charge variation, and n the atomic charge density.